1981
DOI: 10.1083/jcb.90.2.312
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of proinsulin- and proglucagon-converting activities in isolated islet secretory granules.

Abstract: The conversion of proglucagon and proinsulin by secretory granules isolated from both prelabeled and unlabeled anglerfish islets was investigated . Either granules isolated from tissue labeled with [3H]tryptophan and [14 C]isoleucine or ["S]cysteine, or lysed granules from unlabeled tissue to which exogenously labeled prohormones had been added were incubated under various conditions . Acetic acid extracts of these granule preparations were analyzed for prohormone and hormone content by gel filtration . Both p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
36
1

Year Published

1982
1982
1989
1989

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(45 citation statements)
references
References 49 publications
8
36
1
Order By: Relevance
“…Its activity was inhibited by leupeptin, p-chloromercuribenzoate, and pepstatin A, but not by serine or metalloprotease inhibitors. A thiol protease has also been implicated in the conversion ofproinsulin, proglucagon, and prosomatostatin in anglerfish islets (32,33). This acidic protease, which may be' bound to the secretory granule membrane, has an.inhibitor profile qualitatively similar to that reported here.…”
Section: Resultssupporting
confidence: 67%
“…Its activity was inhibited by leupeptin, p-chloromercuribenzoate, and pepstatin A, but not by serine or metalloprotease inhibitors. A thiol protease has also been implicated in the conversion ofproinsulin, proglucagon, and prosomatostatin in anglerfish islets (32,33). This acidic protease, which may be' bound to the secretory granule membrane, has an.inhibitor profile qualitatively similar to that reported here.…”
Section: Resultssupporting
confidence: 67%
“…As expected for a non-receptor mediated process, kidney extraction varied conversely to liver extraction, being highest for human proinsulin and lowest for insulin. It is concluded that the kinetics of human proinsulin conversion intermediates depends upon the site of cleavage and deletion and is intermediate between those of insulin and intact human proinsulin.Key words: Biosynthetic human proinsulin, conversion intermediates, 123-I-labelling, scintillation scanning.Most of proinsulin is converted to insulin inside the B cells of the pancreas, a process resulting from the interplay of several endopeptidases, different from trypsin itself [1][2][3]. Recently, two distinct site-specific endopeptidases regulated by calcium concentration and pH were identified in a B granule fraction of rat insulinoma [4].…”
mentioning
confidence: 99%
“…Most of proinsulin is converted to insulin inside the B cells of the pancreas, a process resulting from the interplay of several endopeptidases, different from trypsin itself [1][2][3]. Recently, two distinct site-specific endopeptidases regulated by calcium concentration and pH were identified in a B granule fraction of rat insulinoma [4].…”
mentioning
confidence: 99%
“…This enzyme activity may be related or similar to other processing enzymes with acidic pH optima identified in pancreatic islet secretory granules of angler fish and rat pancreas (Fletcher et al, 1980(Fletcher et al, , 1981 and adrenal chromaffin granules (Mizuno et al, 1982;Evangelista et al, 1982;Troy and Musacchio, 1982). These enzymes have been defined on the basis of cleavage of pro-insulin, pro-glucagon, pro-somatostatin and/or enkephalin precursors.…”
Section: Processing Enzymes: Cleavage At Paired Basic Amino Acidsmentioning
confidence: 69%